Value of Ralgro® implants in feedlot steers previously maintained on at high endophyte-infected fescue hay - Corah, L.R.; Brazle, F.K.; Blecha, Frank; Reddy, P.G.; Wary, R.E. Jr.; Klindt, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steers previously fed high-endophyte fescue hay showed a greater response of Ralgro® implants than those fed a low-endophyte hay. The mode of action for this response was not explained by cellular immune system responses or variability in prolactin levels.
Keywords: Beef; Stockers; Finishing; Endophyte; Fescue; Ralgo